Cytotoxicity and antiviral activity of electrochemical – synthesized silver nanoparticles against poliovirus - Huy, Tran Quang; Hien Thanh, Nguyen Thi; Thuy, Nguyen Thanh; Chung, Pham Van; Hung, Pham Ngoc; Le, Anh-Tuan; Hong Hanh, Nguyen Thi (Journal of virological methods, 2017)
•Silver nanoparticles (AgNPs) have been eco-friendly synthesized by the electrochemical method.•Electrochemical – synthesized AgNPs are non-toxic to cell cultures at high concentrations (up to 100ppm).•Electrochemical – synthesized AgNPs could inhibit non-enveloped viruses at low concentrations (around 3.13ppm). Silver nanoparticles (AgNPs) have been proven to have noticeable cytotoxicity in vitro and antiviral activity against some types of enveloped viruses. This paper presents the cytotoxicity and antiviral activity of pure AgNPs synthesized by the electrochemical method, towards cell culture and poliovirus (a non-enveloped virus). Prepared AgNPs were characterized by ultraviolet–visible spectroscopy, energy-dispersive X-ray spectroscopy and transmission electron microscopy. Before incubation with poliovirus, different concentrations of AgNPs were added to human rhabdomyosarcoma (RD) cell monolayers seeded in 96 well plates for testing their cytotoxicity. The in vitro cytotoxicity and anti-poliovirus activity of AgNPs were daily assessed for cytopathic effect (CPE) through inverted light microscopy. CPE in the tested wells was determined in comparison with those in wells of negative and positive control. Structure analysis showed that AgNPs were formed with a quasi-spherical shape with mean size about 7.1nm and high purity. No CPE of RD cells was seen in wells at the time point of 48h post-incubation with AgNPs at concentration up to 100ppm. The anti-poliovirus activity of AgNPs was determined at 3.13ppm corresponding to the viral concentration of 1TCID50 (Tissue Culture Infective Dose) after 30min, and 10TCID50 after 60min, the cell viability was found up to 98% at 48h post-infection, with no CPE found. Whereas, a strong CPE of RD cells was found at 48h post-infection with the mixture of AgNPs and poliovirus at concentration of 100TCID50, and in wells of positive controls. With mentioned advantages, electrochemical-synthesized AgNPs are promising candidate for advanced biomedical and disinfection applications.